A Stepped Care Model of Patient Navigation to Enhance Engagement with Perinatal Mental Health Care (Mary Ann Liebert, 2020)
During the perinatal period, women are at increased risk for developing perinatal mood and anxiety disorders (PMADs). As perinatal mental health screening efforts increase, significantly more women will be identified who require mental health services. Evidence-based treatments exist, yet many women do not receive adequate care. Patient navigation (PN) offers a promising patient-centered approach to improve treatment attendance and engagement. The purpose of this study is to describe the development of a stepped care PN service at an intensive outpatient program for women with PMADs. Our experience incorporating this model of PN revealed significant features that may guide other treatment care facilities to adopt this service to increase identification and connection to care.